Improvement Viscosity Index of Lubricating Engine Oil Using Low Molecular Weight Compounds - Idrees, Shenwar A.; Mustafa, Lawand L.; Saleem, Sabah S. (Science Journal of University of Zakho, 2019)
the effect of polarity of solvent on the viscosity and viscosity index of lubricating engine oil has been studied using ethanol as an example of polar solvent and toluene as an example of non-polar solvent at different solvent ratios and ambient temperature and additionally other experiments have been done at five different temperatures including 100 oC. So that, the activation energy of viscous flow (Ea) was calculated, and for this purpose Arrhenius viscosity-temperature dependence has been applied and the results were 42.128, 29.256 and 35.417KJ/mole for lubricating engine oil mixed with ethanol, toluene and no additives in turn. It additionally shows that adding polar solvent to lubrication engine oil viscosity increases this may be due to the fact of strong inter molecular forces that found in polar molecules such as hydrogen bonding in ethanol makes the solution forces stronger as a result higher viscosity. However, adding non-polar solvent decreases viscosity because of small size of toluene and both paraffinic lubricating oil and toluene have same London dispersion inter molecular forces. Last not least, the result shows that engine oil mixed with non-polar molecule gives more temperature stability than that of polar molecule giving viscosity index (VI) 366 and 580 respectively.
Keywords: Engine Oil; Kinematic Viscosity; Viscosity Index